Metastatic pulmonary calcification on bone scintigraphy of a patient with lupus nephritis and end-stage renal disease - Nina H. Cheng, MS; Yi Li, MD; Gang Cheng, MD, PhD (Radiology Case Reports, 2023)
A 65-year-old male complaining of low back pain was noted to have diffuse, homogenous bilateral lung uptake on Tc-99m methylene diphosphate (Tc99m-MDP) bone scintigraphy. The patient had no prior history of pulmonary disease with no apparent respiratory symptoms at time of imaging, but did endorse a long history of lupus nephritis and end-stage renal disease on hemodialysis. Review of prior chest CT and chest X-ray imaging over the last 5 years revealed diffuse ground-glass opacities and extensive parenchymal calcifications, consistent with metastatic pulmonary calcification. These radiological findings were further corroborated by laboratory studies, which demonstrated longstanding secondary hyperparathyroidism with a most recent work-up including an iPTH level of 1251 pg/mL. The differential diagnosis of bilateral, diffuse Tc99m-MDP uptake on bone scintigraphy includes tracer contamination, pulmonary etiologies such as pleural effusion or mesothelioma, metabolic diseases such as metastatic pulmonary calcification, and genetic diseases including pulmonary alveolar microlithiasis. In the setting of longstanding renal dysfunction and chronic hypercalcemia as in this patient, such radiological findings are a classic presentation of metastatic pulmonary calcification.